BATASAN KONSEP QIWAMAH DALAM RELASI SUAMI ISTRI: ANALISIS KEWENANGAN DAN TANGGUNG JAWAB SUAMI BERDASARKAN PASAL 79 KOMPILASI HUKUM ISLAM - Harapan Simamora; Amar Adly; Heri Firmansyah (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2026)
This study aims to analyze the concept of qiwāmah from the perspective of Islamic law, examine the legal position of the husband as the head of the family under Article 79 of the Compilation of Islamic Law (Kompilasi Hukum Islam), and identify the limits of the husband's authority and responsibilities within marital relations. This research employs normative legal research using statutory and conceptual approaches. The data were collected through library research on the Qur'an, Hadith, the Compilation of Islamic Law, and relevant scholarly literature, and were analyzed qualitatively using a descriptive-analytical method. The findings reveal that qiwamah constitutes a mandate of leadership based on the husband's responsibility to provide financial support, protection, guidance, and care for the family. Article 79 of the Compilation of Islamic Law does not grant the husband absolute authority; rather, it places his leadership within the framework of balanced rights and obligation.